(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the frequency of insulin resistance among patients with PCOS. To determine association between BMI and insulin resistance among patients with PCOS. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at the Obstetrics and Gynaecology Unit 3, Civil Hospital, Karachi from 22 February 2021 to 22 August 2021. Materials and Methods: A total of 168 diagnosed cases of PCOS were included in this study. All patients was assessed for Insulin resistance as per operational definition. All data such as age parity BMI, place of residence, socioeconomic status, marital status, duration of all co morbid was recorded on predesigned Performa. Results: The average age of the patients was 27.59±5.15 years. Frequency of insulin resistance among patients with PCOS was 54.17% (91/168). Association of insulin resistance and body mass index was significantly high. Rate of insulin resistance was significantly high with overweight and also obese cases (p=0.0005). Conclusion: In conclusion majority of the overweight/obese PCOS patients showed higher insulin resistance& lower insulin sensitivity vs. their normal weight counterparts. PCOs women are more prone to adiposity and excess body mass index was associated with Insulin Resistance. Consequently, Insulin Resistance disorders androgen profile and threatens metabolic and reproductive health across life span, accordingly, health strategy needs to be screened for the diagnosis of Insulin Resistance in all young PCOs overweight/obese women.